Optimization of Irrigation and Herbicides Using Artificial Intelligence in Agriculture - Vathsala , Atluri Vani; H. N., Lakshmi; Yedukondalu, Gangolu; Seshagiri Rao, Channapragada Rama; Kotha, Mahesh; Changala, Ravindra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Technological aspects play a key role in the economy of country. The usage of technologies in various fields makes automation strong. The integration of new technologies for agriculture era gives a great yield. Demand for food with respect to the population is a great deal. Huge population required tremendous food requirement which cannot be possible with the conventional agriculture methods. In this paper we introduced a new method for agriculture with Artificial Intelligence became a new trend set. Our approach saved crop yield from various geological factors. The primary objective of our work was how various AI applications used in the domain of agriculture sector and increases the fertility of the soil. The vase survey we conducted for this paper was helped us for current set ups for the agriculture through weeding, robots and drones. We focused mainly on automated weeding techniques and sensing issues of water of soil. 94% of the pesticides produced are to protect he crop and to increase the production of crop. But this leads many hazardous issues of environments and humans. By using KNN (K-nearest neighborhood) and LRC (Logical Regression Classification) algorithms we got the predicted value of 88.5%.